The Effect of QAR (Question-Answer Relationships) Strategy to ImproveStudents’ Reading Comprehension - putri asi lestari (Universitas Pahlawan Tuanku Tambusai, 2021)
The goal of the QAR strategy is helping the students in reading comprehension actively by analyzing various steps of questions. QAR (Question-Answer Relationships), which helps the students to answer the question based on the text. QAR is the best strategy that helps students in answering question and comprehending the text more effectively. This research was an experimental research. It was conducted at Pondok Pesantren Miftahul Muarrif which located on kampar regency. The population of this research was the eight year students of Pondok Pesantren Miftahul Muarrif in the second semester. They consisted of 123 students, which divided into 3 classes. The reason to choose eight year students in using QAR technique was this technique appropriate to intermediate level of students. This research focuses of QAR Strategy on students’ Reading Comprehension. The instrument of this research is reading test. The data collection technique that writer used to analyzed data is t-test. The result of this study is taken from the quantitative data. It can be seen that there is improvement from the score pre-test (47.9) to that of post test (74,82) for experimental class and also the t-table 1.99 is smaller than t-observed 12.4. Moreover, it can be seen that after being taught by using QAR (Question-Answer Relationship) strategy, there is increasing of the students’ reading comprehension and they can answer the question with more efficiently. The students can analyze how and where to answer the question effectively The results of these tests were taken as data of this research.